(untitled) (The Peerian Journal, 2022)
The current research contained the first chapter, which dealt with the research problem and the need for it, where the researcher presented the problem in an extensive manner and then ended with the question that summarized that problem with the following question ((What is the impact of contemporary dialectic in achieving acceptance and rejection in fashion designs)) and also included the importance and objective of research and objective limits, the definition of terminology and the second chapter dealt with multiple axes that were dealt with according to the link with the title of the research, where the first topic contained the dialectic of reception beyond the concept of modernity, while the second topic contained the impact of artistic currents in achieving contemporary, and the third was the ideology of demographic variables in the formation of design products, while the third chapter contained the research methodology and the researcher’s reliance on the descriptive-analytical approach. As for the fourth chapter, it contained the results, the most important of which are.